Pengembangan Media Pembelajaran Video Berbasis Benime Pada Matakuliah Sejarah Perekonomian Dunia - Muhammad Naharuddin Arsyad; Debi Setiawati; Faizah Ulumi Firdausi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this research is to find out (1) the process of developing benime-based video learning media in world economic history courses, (2) the feasibility of benime-based video learning media in world economic history courses, and (3) student responses to video learning media based on benime in the course of world economic history. This type of research is development research which contains the development of Benime-based video learning media in world economic history courses. The development model used in this study consists of three stages, namely the define, design, develop stages. The results of the study show that the developed benime-based video learning media is very suitable for use in the learning process. From material feasibility experts, the product obtained a value of 78%. From media experts, product feasibility obtained a score of 82%. From the opinion of students, product feasibility obtained a value of 84% with very feasible criteria.